Cost-Utility of Sildenafil for Persistent Pulmonary Hypertension of the Newborn - Evers, Patrick D.; Critser, Paul J.; Cash, Michelle; Magness, Melissa; Hoelle, Susan; Hirsch, Russel (American Journal of Perinatology, 2020)
Objective While advanced therapies for severe persistent pulmonary hypertension of the newborn (PPHN) such as inhaled nitric oxide (iNO) and extracorporeal membrane oxygenation (ECMO) are standard treatments in high-income countries, these therapies are often unavailable in resource-limited settings such as middle-income countries. However, there are small clinical trials illustrating the efficacy of sildenafil at reducing mortality in PPHN. This analysis sought to determine the cost-utility of enteral sildenafil for the treatment of severe PPHN.Study Design A Markov-state transition model was constructed for the two clinical approaches to compare costs, clinical outcomes, and quality of life: (1) “conventional,” (2) “sildenafil.” The impact of sildenafil was modeled as a relative risk modifier of the conventional strategy's mortality risk. Transitional probabilities, costs, and utility metrics were extracted from the literature. Sensitivity analyses for each model input as well as 100-patient Monte Carlo simulations were used to test the durability of the model conclusion.Results The sildenafil strategy was cost-effective for upper but not lower middle-income countries with an incremental cost-effectiveness ratio of $2,339 per quality-adjusted life year. This conclusion was durable across a wide-range of model assumptions; the sildenafil strategy only failed to meet criteria for cost-effectiveness when sildenafil therapy had a mortality relative risk efficacy of >0.89, if life expectancy in that country is <40 years, or if the lifetime forecasted costs of a survivor's life was quite high.Conclusion Enteral sildenafil is a cost-effective intervention for severe PPHN for upper middle-income countries where ECMO and iNO are not available.Key Points
Keywords: pediatrics; pulmonary hypertension; cost-effectiveness; global health